Security Challenges and the Proliferation of Small & Light Arms in Nigeria: Implication for National Development - Mohammed Ghani Dass; Muhammad Auwal Sulaiman (Khazanah Hukum)
It is apt to note that the central impediment to sustainable peace and security is the constant and continued proliferation of small and light weapons (SALW). The escalation of these arms contributed/became a threat to peace and tranquillity in Nigeria and precipitated inter-ethnic conflicts leading to an insurgency on a light scale. The paper aims to examine the continued proliferation of small and light arms and the challenges to national security with particular reference to Nigeria and the sources. The study employed descriptive as its methodology anchored on the frustration framework within the secondary data source. The study unveils that arms proliferation is centred on the porosity of the Nigerian borders. This development contributes in no small measures precipitated security challenges. The paper concludes as part of its recommendations that governments should strengthen the security activities at the Nigerian border and train personnel on border-related issues. The paper concludes as a matter of urgency government should embark on the gainful employment of youths to subdue the activities of insurgents and terrorist attacks in the six (6) geopolitical zones of Nigeria.